Predicting chemosensitivity to gemcitabine and cisplatin based on gene polymorphisms and mRNA expression in non-small-cell lung cancer cells. (January 2015) - Meng, Xiangning; Wang, Geng; Guan, Rongwei; Jia, Xueyuan; Gao, Wei; Wu, Jie; Yu, Jingcui; Liu, Peng; Yu, Yang; Sun, Wenjing; Dong, Haiying; Fu, Songbin
Aim: We used a panel of 17 non-small-cell lung cancer cell lines to investigate whether the presence of polymorphisms in the RRM1, ERCC1, ABCB1 and MTHFR genes and alterations in their mRNA expression can affect the in vitro chemosensitivity to cisplatin and gemcitabine.Materials & methods: Polymorphisms in these genes were evaluated by direct sequencing. mRNA expression levels were assessed by realtime PCR. In vitro chemosensitivity to cisplatin and gemcitabine was expressed as IC50 values, using the MTT (3-[4, 5-dimethylthiazol-2-yl]-2, 5-diphenyltetrazolium bromide) assay.Results: There was a significant, positive correlation between RRM1 mRNA expression and IC50 values for gemcitabine (r = 0.6533, p = 0.0045), and there was a significant, negative correlation between ABCB1 mRNA expression and IC50 values for cisplatin (r = -0.5459, p = 0.0287). When examining the association between the polymorphisms and IC50, we found that only the MTHFR 1298A>C polymorphism showed a tendency to be more chemosensitive to gemcitabine (p = 0.0440).Conclusion: These in vitro results suggest that mRNA expression levels of the RRM1 and ABCB1 genes may be useful indicators of chemosensitivity to gemcitabine and cisplatin, respectively. The MTHFR 1298A>C polymorphism was associated with gemcitabine chemosensitivity, which require further functional analysis with co-expressed genes and should be explored in prospective clinical studies to determine its potential clinical application as a predictive biomarker. Original submitted 11 February 2014; Revision submitted 3 November 2014